Comparative Study on Massage Therapy with Coconut Oil and without Oil on Body Weight in Low Birth Weight Preterm Neonates - Dr Binoy Shankar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and Aim Prematurity and low birth weight are important causes for neonatal mortality and hospitalization. The present study aimed to investigate the benefit of massage therapy with coconut oil and massage alone on the weight gain of low birth weight preterm neonates admitted in Neonatal Intensive Care Unit (NICU). Methods and Results This observational study was performed on 60 stable preterm neonates hospitalized in the NICU of a tertiary care hospital. They were divided into two groups: massage with coconut oil and massage alone. These groups were compared on the basis of weight gain during first fifteen days. In the massage with coconut oil group, the mean weight gain on the 7th day was 119.6±25.85 gr and on the 15th day was 297± 37.52 gr, whereas in the massage alone group the mean weight gain on the 7th day was noted to be 70.9±17.27 gr and on the 15th day was 196±16.52 gr. Significant differences were observed between the massage with coconut oil group and the massage alone group (p< 0.0001). Conclusion The findings of this study suggest that transcutaneous feeding with coconut oil in low birth weight preterm neonates can result in better weight gain velocity as compared to massage alone group.